Strategic decisions on urban built environment to pandemics in Turkey: Lessons from COVID-19 - Md Moynul Ahsan (Journal of Urban Management, 2020)
COVID-19 is a global pandemic where urban built environment is facing significant challenges. Deploying robust strategic planning and decisions on built environment can overcome or reduce such challenges. These strategies can help to inform, assist urban citizens as well as address anticipated threats of pandemics. From the Ottoman Empire to modern Turkey has taken several strategic measures for its urban built environment in order to ensure health and safety issues of the urban citizen. Based on secondary based research, this study reviews the historical background on different measures on the urban built environment and giving special attention on COVID-19 until its normalisation phase started on June 1, 2020. This study recommends that centralised decision making and active participation and implementation at the local level can make successful to combat pandemics. This study also recommends that adequate provision of place, safety, health-related issues with an integrated manner are needed to form healthy urban built environment. In addition, safe water, green environment, adaptation-based strategies on climate change, comprehensive community planning, de-densifying inside buildings etc. seems to be a solution for future urban built environment design.
Keywords: 710; Before new normal; COVID-19; Strategic decision; Turkey; Urban built environment